2019
DOI: 10.1002/ajpa.23828
|View full text |Cite
|
Sign up to set email alerts
|

CT‐based sex estimation on human femora using statistical shape modeling

Abstract: Objectives: Estimating the sex of decomposed corpses and skeletal remains of unknown individuals is one of the first steps in the identification process in forensic contexts.Although various studies have considered the femur for sex estimation, the focus has primarily been on a specific single or a handful of measurements rather than the entire shape of the bone. In this article, we use statistical shape modeling (SSM) for sex estimation. We hypothesize that the accuracy of sex estimation will be improved by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…It is often achievable by using anthropometric parameters derived from anonymous skeletal structures that readily showed sexual dimorphism. 16,17 Based on the results of this study, proximal femoral dimensions showed non-significant bilateral differences with the right side having higher values in all parameters of study except femoral neck length in males (Table 1) and femoral neck diameter in females ( Table 2). The results further showed prominent sexual dimorphism in all parameters of study with the males having significantly (p<0.05) higher values than their female counterparts (Table 3).…”
Section: Discussionmentioning
confidence: 70%
“…It is often achievable by using anthropometric parameters derived from anonymous skeletal structures that readily showed sexual dimorphism. 16,17 Based on the results of this study, proximal femoral dimensions showed non-significant bilateral differences with the right side having higher values in all parameters of study except femoral neck length in males (Table 1) and femoral neck diameter in females ( Table 2). The results further showed prominent sexual dimorphism in all parameters of study with the males having significantly (p<0.05) higher values than their female counterparts (Table 3).…”
Section: Discussionmentioning
confidence: 70%
“…Based on 61 femora from routine postmortem CT scans, a previously published statistical shape model of the human femora was used [ 12 ]. To create this model, a non-rigid registration algorithm [ 29 ] was used and 20 principal components were defined to represent 99% of the shape variance [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…Based on 61 femora from routine postmortem CT scans, a previously published statistical shape model of the human femora was used [ 12 ]. To create this model, a non-rigid registration algorithm [ 29 ] was used and 20 principal components were defined to represent 99% of the shape variance [ 12 ]. Using Autodesk Inventor (Autodesk Inc., San Rafael, USA), biplanar DFO were created with a horizontal osteotomy angle of 25° for MCW and 18° for LOW, respectively (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, dentition staging and development are highly useful in age assessment of juveniles [ 59 ]. Some techniques, such as statistical shape modeling, require 3D models extracted from PMCT data, and these models could be automatically extracted using automated segmentation [ 60 ].…”
Section: Possible Applications Of Deep Learning Techniques In Pmctmentioning
confidence: 99%